Review and Analysis of National Monitoring Systems for Antimicrobial Resistance in Animal Bacterial Pathogens in Europe: A Basis for the Development of the European Antimicrobial Resistance Surveillance Network in Veterinary Medicine (EARS-Vet) - Mader, Rodolphe; Muñoz Madero, Cristina; Aasmäe, Birgit; Bourély, Clémence; Broens, Els M.; Busani, Luca; Callens, Bénédicte; Collineau, Lucie; Crespo-Robledo, Paloma; Damborg, Peter; Filippitzi, Maria-Eleni; Fitzgerald, William; et al. (Frontiers in Microbiology, 2022)
The monitoring of antimicrobial resistance (AMR) in bacterial pathogens of animals is not currently coordinated at European level. To fill this gap, experts of the European Union Joint Action on Antimicrobial Resistance and Healthcare Associated Infections (EU-JAMRAI) recommended building the European Antimicrobial Resistance Surveillance network in Veterinary medicine (EARS-Vet). In this study, we (i) identified national monitoring systems for AMR in bacterial pathogens of animals (both companion and food-producing) among 27 countries affiliated to EU-JAMRAI, (ii) described their structures and operations, and (iii) analyzed their respective strengths, weaknesses, opportunities and threats (SWOT). Twelve countries reported having at least one national monitoring system in place, representing an opportunity to launch EARS-Vet, but highlighting important gaps in AMR data generation in Europe. In total, 15 national monitoring systems from 11 countries were described and analyzed. They displayed diverse structures and operations, but most of them shared common weaknesses (e.g., data management and representativeness) and common threats (e.g., economic vulnerability and data access), which could be addressed collectively under EARS-Vet. This work generated useful information to countries planning to build or improve their system, by learning from others’ experience. It also enabled to advance on a pragmatic harmonization strategy: EARS-Vet shall follow the European Committee on Antimicrobial Susceptibility Testing (EUCAST) standards, collect quantitative data and interpret AMR data using epidemiological cut-off values.